2013
DOI: 10.4103/1119-3077.116889
|View full text |Cite
|
Sign up to set email alerts
|

Presence of chaperones during pelvic examinations in southeast Nigeria: Women′s opinions, attitude, and preferences

Abstract: We conclude that most southeastern Nigerian women would prefer their pelvic examinations to be done by a female physician or to be attended by a nurse chaperone if the examining physician is a male. We recommend a routine offer of chaperones during such examinations while respecting the patients' right to refuse the offer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…This information will be important to female clinicians who have traditionally less frequently offered a chaperone during breast examinations. 6 8 11 12 This study, as others, 12 14 demonstrates that women are more likely to decline the offer of a chaperone when the examining clinician is female; 61.45% declined a chaperone offered by a female clinician compared to 3.82% declining if the clinician was male. The reverse of this is that nearly 40% of women will still choose a chaperone even with a female clinician.…”
Section: Discussionsupporting
confidence: 51%
“…This information will be important to female clinicians who have traditionally less frequently offered a chaperone during breast examinations. 6 8 11 12 This study, as others, 12 14 demonstrates that women are more likely to decline the offer of a chaperone when the examining clinician is female; 61.45% declined a chaperone offered by a female clinician compared to 3.82% declining if the clinician was male. The reverse of this is that nearly 40% of women will still choose a chaperone even with a female clinician.…”
Section: Discussionsupporting
confidence: 51%
“…concerning pelvic examinations in south-east, Nigeria, it was revealed that 51.7% of the women in the study preferred to be examined by a female doctor. [24] The percentage that preferred a male sonologist (8.8%) in our study is higher than the 1.7% observed by Atalabi et al . [13] Similarly, a study conducted among seven male and nine female physicians in a group family medicine practice in Montreal, Que Canada, suggested that being a male primary care physician remains associated with lower rate of cervical cancer screening.…”
Section: Discussioncontrasting
confidence: 83%
“…Additionally, previous published studies on the use of chaperone in Nigeria have focused exclusively either on assessing the opinions, attitude, and preferences of women to the presence of chaperones during pelvic examinations or attitudes of a particular medical discipline such as gynaecologist or general practitioners to medical chaperoning [3,11,12]. In one of these studies, scarcity of personnel to serve as chaperones is the greatest challenge to the implementation of this policy.…”
Section: Volume 2 | Issuementioning
confidence: 99%
“…Despite this trend, the frequency of chaperone use has generally remained low especially in Nigeria [3,11]. This may be because; as yet the Nigerian Code of Medical Council does not have a policy on mandatory chaperone use in medical consultation [11].…”
mentioning
confidence: 99%